The development and evaluation of an integrated virtual patient case study and related online resources for person-centred nursing practice - Orr, F.; Kelly, Michelle; Virdun, C.; Power, T.; Phillips, A.; Gray, J. (2021)
Ensuring students develop person-centred practice for diverse groups of people across health care settings is an important outcome of undergraduate nursing education. This paper presents the development and evaluation of a learning innovation, an integrated virtual patient case study and complementary online resources for person-centred nursing practice. The virtual patient case study of an Australian Aboriginal woman diagnosed with breast cancer was integrated within four core subjects of a Bachelor of Nursing program, for a total of 600 second-year students. The evaluation of this learning strategy was encouraging. Students reported that the online learning activities were engaging, particularly due to the level of realism, their understanding of Aboriginal Peoples’ healthcare needs increased, and they developed therapeutic communication skills, applicable in a variety of healthcare contexts. Staff concerns about student wellbeing when learning sensitive content online were unfounded. When carefully planned, a virtual patient case study and online learning resources can support students to enhance their person-centred nursing practice. Further evaluation, including student outcomes through assessment, is an important next step.